Komunikasi Pesan Religius untuk Penanaman Nilai-Nilai Islam Pada Anak Usia Dini di BA Aisyiyah Gumiwang - Naningsih, Septi; Hanif, Muh. (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
It is impossible for humans to carry out their role as bearers of the mandate of Allah SWT in this world without communication. Likewise, every parent should talk to their children from childhood, especially about matters related to religious values. Religion functions as identity, a moral source, a guide to truth, and even spiritual guidance for humans. Religious education in the family is very important and mandatory because it will influence children's morality so that they do not fall into promiscuity which is dangerous for their future. Children at an early age experience rapid physical and mental growth. It is very important to encourage children to learn because of this rapid development and growth. This research is research that uses qualitative methods with data collection using interview and documentation techniques. The results of this research are: In the psychology paradigm, there are at least 4 theories related to early childhood development, including social, cognitive and constructivist theories: Social Cognitive Theory, teaches the idea that the social environment is where most human learning occurs. Furthermore, they act according to their beliefs about their abilities and the expected outcomes of their actions. Cognitive Development Theory. teaches that the thought process a person has, which includes their ability to relate, assess, and consider what happens or happens to them. There are 4 stages of cognitive development based on age: a. Sensory (sensory motor) stage, b. Preoperational stage (preoperational), c. concrete operational stage (concrete operational), d. formal operational stage (formal operational), Constructivism theory is a learning theory that aims to encourage students to actively discover and build their own knowledge and improve their abilities and skills independently.